Identification of Colisepticemia in Broiler Chicken in Tabanan, Bali - Devira, Dinda; Ketut Tono Pasek Gelgel; I Ketut Berata (Sekolah Kedokteran Hewan dan Biomedis, 2025)
Colisepticemia is a condition where Escherichia coli and its toxins have spread to tissues or organs that can cause organ damage or inflammation. Colisepticemia is a sign of acute colibacillosis in poultry which can result in death and in its subacute form is characterized by pericarditis, airsacculitis and perihepatitis. The incidence of colibacillosis in poultry can result in economic losses due to reduced production, increased medical costs, and even death. The aim of this study was to establish a diagnosis of the death of 15 days old broiler chicken. Based on the necropsy results, characteristic anatomical pathology was found in the form of fibrin membranes on the heart and liver, as well as lesions on other organs. Identification and isolation of bacteria in the laboratory using samples from the heart, liver and intestines showed positive results for Escherichia coli. Parasitological examination using feces did not reveal any parasitic agents involved in this case. Based on clinical symptoms, anatomical pathology examination, histopathology, culture and identification of bacteria, it can be concluded that the cause of chicken death was colisepticemia caused by Avian Pathogenic Escherichia Coli (APEC).